Association of Vitamin D Receptor Gene SNP BsmI (1544410) with Axial Spondyloarthritis in Iraqi Patients Treated with Infliximab - Drewil, Abdullah H.; Rasheed, Manal K.; Jassim, Nizar A. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Axial spondyloarthritis is a chronic inflammatory disorder driven by tumor necrosis factor alpha and the interleukin-23/interleukin-17 pathway. Tumor necrosis factor alpha inhibitors such as infliximab improve outcomes, but responses vary, suggesting genetic influences; vitamin D receptor polymorphisms—particularly BsmI ( rs1544410) may modulate disease activity and therapeutic response. Objectives: This study aimed to investigate the association between the VDR BsmI polymorphism and disease activity, as well as infliximab treatment response in patients with Axial spondyloarthritis. Methods: A cross-sectional study was conducted on 150 AxSpA patients (108 males, 42 females) receiving infliximab for at least three months. VDR BsmI genotyping was performed using PCR-RFLP. The study took place at the Rheumatology Clinics of Baghdad Hospital, Medical City, Iraq, with ethical approval from the Department of Biochemistry, College of Medicine, University of Baghdad. Statistical analysis included ANOVA, odds ratio estimation, and Pearson correlation, with significance defined as p ≤ 0.05. Results: BsmI genotype distribution was AA (28%), AG (46%), and GG (26%), with allele frequencies of 51% (A) and 49% (G). No significant association was found between BsmI polymorphism and infliximab duration. However, a significant association was observed with disease activity (p = 0.008). The AA and AG genotypes were also significantly associated with male gender (p = 0.01). No significant correlations were found with other clinical features including inflammatory back pain, Urinary tract infection , enthesitis, uveitis, dactylitis, psoriasis, or colitis. Conclusion: The GG genotType was linked to an increased likelihood of inactive disease, while the AA genotype was associated with an increased risk of low disease activity. These findings suggest VDR BsmI polymorphism may influence AxSpA disease activity and response to infliximab